Epidemiological-forensic analysis of electro cutions in Colombia during 2010-2014 (2017)
Introduction : This study allowed us to identify the characteristics of individuals electrocuted in Colombia in the period 2010-2014, both in sociodemographic variables and in the main findings during necropsy. Materials and methods: A descriptive, retrospective observational study was carried out with information obtained from the necropsy reports of the National Institute of Forensic Medicine and Forensic Sciences. Results and discussion: 899 cases of electrocution were analyzed; 92.8% were men, 52.4% of the people were working at the time of death, and 71.5% of the electrocuted individuals were from the urban area of Colombia. The mortality rates of the cities with the highest frequency of electrocutions in Colombia were determined and compared with the national rate. 63.4% of electrocutions were by high voltage and the sites of entry and exit of the current were deter mined, with a proportion of cases with extensive burn. A statistically significant association was found between voltage and skin findings; however, no association was found between voltage type and internal examination findings. Most of the deaths were accidental, while a case of homicide and a case of possible suicide were found. Conclusions: Deaths due to electrocution represent a hidden problem in many Colombian cities, with sociodemographic characteristics susceptible to prevention by the governmental bodies. The forensic expert must know the typical and atypical concepts and findings of electrocutions according to the context of facts, type of voltage and findings to make an appropriate approach to necropsy.